Expanded Dengue Syndrome: A Growing Concern - Zahiruddin, Mohammad; Rishad, Mahbub Mayukh (Bangladesh Journal of Medicine, 2022)
Dengue is not only confined to its classical presentation of high-grade fever, body ache, shock, plasma leakage and thrombocytopenia. Itinvolves multiple organ like brain, heart, liver, abdomen, kidney, lungs, thyroid and causing concerning morbidity and mortality. In this review article we have tried to focus on the different variety of presentation which is now called Expanded Dengue Syndrome. This review article will be helpful to physician to combat Dengue virus where it is endemic. Bangladesh J Medicine 2022; 33: 5-9